Secondary Hypertension due to Abdominal Coarctation; How do we identify and manage it?: A Case Report - Oktafin Srywati Pamuna; Novi Kurnianingsih; Anna Fuji Rahimah; Heny Martini (Heart Science Journal, 2022)
BackgroundCoarctation of the abdominal aorta (AoA) is a very uncommon condition, accounting for 0.5-2 percent of all aortic stenosis cases. We present an 11-year-old child who has been diagnosed with abdominal aorta coarctation. Case IllustrationAn 11-years old boy complained about dizziness since 1.5 years ago with hypertension. He underwent hypertension treatment for 1.5 years with a pediatrician but there is no improvement in his blood pressure. His current blood pressure was 150/95 mmHg in upper extremities and 120/80 mmHg in lower extremities with three antihypertensives drugs. We found bruit in the abdomen and decreases pulse in lower extremities. An echocardiogram shows no congenital defect. The first was on suspicion of renal stenosis and underwent ultrasonography of the abdomen but was not conclusive. Computed Tomography Angiographic (CTA) showed severe stenosis in the abdominal aorta on level thoracal 11-12. Aortogram shows significant stenosis in the abdominal aorta with a pressure gradient was 47 mmHg. He underwent percutaneous transluminal angioplasty with BMS self-stent implantation. At two months of follow up his blood pressure target was achieved with a minimal dose of oral antihypertensive drugs DiscussionHow to diagnose coarctation of the abdominal aorta is still challenging and often underdiagnosed. Patients with young age and persistent hypertension should be more careful in diagnosis. A  bruit in the abdomen with a weak pulse in the lower extremity raises suspicion of Coarctation of the Abdominal Aorta. An angioplasty procedure, either with or without a stent or a surgery might be used as the primary therapy.